2014
DOI: 10.1155/2014/490589
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimycobacterial Activity of Pakistani Beri Honey Using BACTEC MGIT 960

Abstract: Background. Tuberculosis (TB) is a chronic bacterial disease. Mycobacterium tuberculosis, being the leading member of the MTB complex, is the main cause of tuberculosis worldwide. Tuberculosis is managed with combination of drugs: streptomycin, isoniazid, rifampicin, ethambutol, and pyrazinamide. Over the recent past years resistance against first line antituberculous drugs has emerged rapidly throughout the world resulting in MDR strains. The new threat in the management of MDR-TB is the development of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Over the recent past years, resistance against antituberculous drugs has emerged rapidly, resulting in MDR (Multi Drug Resistant) strains. In vitro activity of Beri honey (from Pakistan) was tested against 21 clinical isolates of MDR-MTB by Hannan and coworkers (2014) [35]. The obtained results clearly demonstrate that Pakistani Beri honey exhibits significant antimycobacterial potential, and three (14%) of the isolates were susceptible at 1% (v/v) honey, while at 2% (v/v) of honey, 18 (86%) isolates were found to be susceptible.…”
Section: Activity Against Mycobacterium Tuberculosismentioning
confidence: 97%
See 1 more Smart Citation
“…Over the recent past years, resistance against antituberculous drugs has emerged rapidly, resulting in MDR (Multi Drug Resistant) strains. In vitro activity of Beri honey (from Pakistan) was tested against 21 clinical isolates of MDR-MTB by Hannan and coworkers (2014) [35]. The obtained results clearly demonstrate that Pakistani Beri honey exhibits significant antimycobacterial potential, and three (14%) of the isolates were susceptible at 1% (v/v) honey, while at 2% (v/v) of honey, 18 (86%) isolates were found to be susceptible.…”
Section: Activity Against Mycobacterium Tuberculosismentioning
confidence: 97%
“…The obtained results clearly demonstrate that Pakistani Beri honey exhibits significant antimycobacterial potential, and three (14%) of the isolates were susceptible at 1% (v/v) honey, while at 2% (v/v) of honey, 18 (86%) isolates were found to be susceptible. All the 21 isolates (n = 21) were susceptible at 3% (v/v) of honey [35]. Honey was also proposed for treatment tuberculosis by Avicenna, a known ancient Persian philosopher and physician.…”
Section: Activity Against Mycobacterium Tuberculosismentioning
confidence: 99%
“…According to Shenoy et al (2012) and Ahmadi-Motamayel et al (2013), honey has a broad spectrum of activities against Gram+ bacteria such as Streptococcus pyogenes (Maddocks et al 2012) and Mycobacterium (Asadi-Pooya et al 2003;Eteraf-Oskouei and Najafi 2013) as well as against Gram-bacteria like Escherichia coli (Adebolu 2005;Voidarou et al 2011;Hegazi et al 2017), Pseudomonas aeruginosa (Shenoy et al 2012), Salmonella typhi, Salmonella paratyphi, Salmonella enterocolitis, Shigella dysenteriae (Cortopassi-Laurino and Gelli 1991;Adebolu 2005;Voidarou et al 2011) and Helicobacter pylori (Atrott and Henle 2009;Lyudmila et al 2015). Several reviews on honey have shown a significant antibacterial and antibiofilm potential against methicillin-resistant Staphylococcus aureus (Sherlock et al 2010;Huttunen et al 2013;Lu et al 2014;Jantakee and Tragoolpua 2015;Ng and Lim 2015;Dimitrios et al 2018;Proaño et al 2021), against multiresistant Mycobacterium tuberculosis (Hannan et al 2014), multiresistant S. typhi (Hussain et al 2015) and against carbapenem-resistant P. aeruginosa (Cooper et al 2014;Dimitrios et al 2018). Honey is an alternative remedy in treating udder infections in veterinary medicine.…”
Section: Properties Of Honeymentioning
confidence: 99%
“…Its most common application is for healing wounds and skin infections [ 27 , 28 , 29 ]. Honey possesses significant antibacterial [ 30 , 31 , 32 ], antiviral [ 33 , 34 ], antifungal [ 27 , 35 , 36 , 37 ], antioxidant [ 27 , 38 , 39 , 40 ], anti-inflammatory [ 41 , 42 , 43 ], antineoplastic [ 28 , 44 ], antimicrobial [ 45 , 46 , 47 ], anticarcinogen [ 48 , 49 , 50 ], antiarrhythmic [ 51 , 52 ], antileishmanial [ 53 , 54 ], antithrombotic, antiplatelet [ 55 , 56 ], antimutagenic [ 57 , 58 ], antinociceptive [ 59 , 60 ], antimycobacterial [ 7 , 61 ], antiproliferative [ 62 , 63 ], and immune-boosting [ 64 , 65 , 66 ] properties. It is also shown to have hypocholesterolemic [ 67 , 68 ], cardioprotective [ 69 , 70 ], antihypertensive [ 71 ], hepatoprotective […”
Section: Medicinal Properties Of Honeymentioning
confidence: 99%